Frames with Intentionally Eccentric W-Shape, C-Shape, and Round HSS Braces - González Ureña, Andrés (2025)
Steel Frames with Intentionally Eccentric Braces (FIEBs) are an innovative Seismic Force-Resisting System (SFRS) that offers significant advantages compared to Concentrically Braced Frames (CBFs).Recent research has shown that the adjustable stiffness and strength of Braces with Intentional Eccentricity (BIEs) with square Hollow Structural Section (HSS) bracing members allows for a better control over the structure’s dynamic response and for a reduction of the capacity-based design forces on the non-energy-dissipating members. In this article, the aptness of W-shapes, C-shapes, and round HSSs to be employed as bracing members in multi-story FIEBs is evaluated preliminarily. To this end, hypothetical buildings with FIEBs based on the three section types as their SFRS are designed using a displacement-based procedure for the seismic hazard of locations in Costa Rica, and their performance is assessed numerically with Non-Linear Response History Analysis (NLRHA). The results show that the three section types produce FIEBs that display a satisfactory seismic response in terms of maximum story drifts and story shears, and that the use of W-shape BIEs results in the most cost-effective designs.